Effect Carrageenan to Biodegradable Plastic From Tubers (Universitas Negeri Semarang, 2019)
Plastic waste can cause serious environmental problems. This can be overcome by various efforts; one of them is by replacing the use of conventional plastic with biodegradable plastic. Biodegradable plastic can be produced from tubers containing starch. The purpose of this study was to explain the suitability of two tuber species with typical protein quality and different starch structures. Starch was obtained from suweg tuber (Amorphophallus campanulatus) and ganyong (Canna edulis Ker). The material invested was obtained by dissolving 4 grams of each starch, each of which was dissolved with distilled water then added with various weight carrageenan. The tensile strength of biodegradable plastic was tested using tensile testing machines, biodegradation of soaked plastics using EM4 (Effective Microorganism) with reduced weight measurements, and Fourier Transform Infra-Red (FTIR) was used to identify the structure of compounds contained in biodegradable plastics. The tensile strength test results of biodegradable plastic from ganyong/canna tubers were 3.35 MPa with elongation of 13.51%, while the plastic from suweg tubers of 2.45 MPa with elongation was 13.68% on the addition of 5% carrageenan, respectively. Plastic degradation testing obtained plastic decomposition up to 100% in 37 days for ganyong and 34 days for suweg, respectively. It showed that the plastics was easily degraded. Identified by FTIR showed chemical structures of OH phenolic alcohols, C = O carbonyls, CO esters, NH amides and amines, and Câ‰¡C alkyne.